Aspek-Aspek Tentang Bantuan Hukum Pada Undang-Undang Nomor 8 Tahun 1981 (KUHAP) - Emilson Atharwan (Belom Bahadat, 2021)
Abstract The purpose of writing this article is to find out the content of Indonesian Law number 8 of 1981 which protects the human rights of suspects / defendants in criminal cases; and to know and understand the mechanisms of legal assistance in criminal cases regulated by the KUHAP, so that human rights can be protected. The method used is the Normative Juridical approach, which is to learn various legal rules and pay attention to the principles related to criminal law, criminal procedure law, regulations on advokad, and provisions on human rights. The sources of legal materials used are primary legal materials and secondary legal materials. The data collection technique used is literature studies. The data analysis used is qualitative descriptive. The results of research on the content of Indonesian Law No.8 of 1981 that protects the human rights of suspects / defendants in a criminal case, are given the principle of presumption of innocence, legal aid, legal assistance, no discrimination, and no torture. Legal aid mechanisms in criminal cases regulated by the KUHAP so that human rights can be protected. To the suspect / defendant given the right to legal aid has been regulated in Law number 19 of 1964 on the basic provisions of judicial power, which is then revoked and replaced by Law number 14 of 1970 (articles 35, 36, and 37) and further stipulated in articles 69 - 74 KUHAP. About the legal assistance it is said in article 69 among others that legal counsel has the right to contact the suspect from the moment of arrest or detention at all levels of examination according to the procedures specified in the Law Keywords: Legal Aid, Advocates, Laws (KUHAP)